Self-assembly of a catechol-based macrocycle at the liquid–solid interface: experiments and molecular dynamics simulations - Saiz Poseu, Javier (2012)
This combined experimental (STM, XPS) and molecular dynamics simulation study highlights the complex and subtle interplay of solvent effects and surface interactions on the 2-D self-assembly pattern of a Schiff-base macrocycle containing catechol moieties at the liquid–solid interface. STM imaging reveals a hexagonal ordering of the macrocycles at the n-tetradecane/Au(111) interface, compatible with a desorption of the lateral chains of the macrocycle. Interestingly, all the triangular-shaped macrocycles are oriented in the same direction, avoiding a close-packed structure. XPS experiments indicate the presence of a strong macrocycle–surface interaction. Also, MD simulations reveal substantial solvent effects. In particular, we find that co-adsorption of solvent molecules with the macrocycles induces desorption of lateral chains, and the solvent molecules act as spacers stabilizing the open self-assembly pattern.